Imaging Informatics Fellowship Curriculum: a Survey to Identify Core Topics and Potential Inter-Program Areas of Collaboration - Makeeva, Valeria (J Digit Imaging, 2019)
New consumer technologies and interoperability standards have dated the first standardized curriculum for imaging informatics fellowships suggested by the Society for Computer Applications in Radiology (SCAR) in 2004 (Journal of digital imaging 17(4):244-248, 2004). Last year, analysis from this institution characterized current state fellowship graduation requirements and broad curriculum topics for the first time in over a decade (SIIM Strategic Plan 2017–2020). However, an updated “core” curriculum has not yet been developed. Using the recent current state analysis as a baseline, we aimed to perform a focused assessment and propose that this would work towards an updated consensus “core” curriculum as outlined by the Society for Imaging Informatics in Medicine (SIIM, previously SCAR) strategic plan. A secondary aim was to identify individual program strengths and weaknesses to foster inter-program collaboration. Using sub-topics from the National Imaging Informatics Curriculum (NIIC), a week-long introductory course for residents, we expanded the original 29 broad curriculum categories identified in last year’s current state analysis into 114 sub-topics. We surveyed imaging informatics fellowship directors to identify sub-topic prioritization on a 5-item Likert scale, teaching methods for each sub-topic, cross-departmental partnerships, and individual program strengths and weaknesses. Only 8% of sub-topics (10/114) received a “definitely” rating with 100% agreement while the majority of sub-topics 77% (88/114) had mixed grading defined by two or fewer “definitely” ratings. These sub-topics mapped to only 4 of the original 29 broad fellowship curriculum categories including Standards, Programming/Development/Software, Infrastructure, and PACS/RIS/Reporting. Our plan is to use consensus topics to build a “core” informatics fellowship curriculum and initiate discussion surrounding mixed grading topics. Knowledge of individual program strengths and weaknesses can be used to foster inter-program collaboration.